The impact of seasonal and price adjustments on the predictability of German GDP revisions - Jens Boysen-Hogrefe; Stefan Neuwirth (Kiel Institute for the World Economy (IfW), 2012)
Releases of the GDP are subject to revisions over time. This paper examines the predictability of German GDP revisions using forecast rationality tests. Previous studies of German GDP covering data until 1997 finds that revisions of real seasonally adjusted GDP are predictable. This paper uses a newly available real-time data to analyze the revisions of real seasonal adjusted GDP, of nominal unadjusted GDP, of the seasonal pattern, and of the GDP deflator for the period between 1992 and 2006. We find that the revisions of the nominal unadjusted GDP are unpredictable, but that the revisions of the price adjustments are predictable. Nevertheless, revisions of real seasonally adjusted GDP are hardly predictable and less well predictable compared to earlier studies. This lower predictability seems to be linked to the finding that revisions of seasonal adjustments are hardly predictable, too, and that their predictability decreased over time.
Keywords: C82; 330; real-time data; GDP revisions; noise; news; forecasting; seasonal adjustment; price adjustment; Sozialprodukt; Statistischer Fehler; Prognoseverfahren; Saisonbereinigung; Preisniveau; Anpassung; Deutschland